2002
DOI: 10.1563/1548-1336(2002)028<0002:brtmar>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Bone Response to Machined and Resorbable Blast Material Titanium Implants: An Experimental Study in Rabbits

Abstract: The aim of the present study was a comparison of implants' responses to a machined surface and to a surface sandblasted with hydroxyapatite (HA) particles (resorbable blast material [RBM]). Threaded machined and RBM, grade 3, commercially pure, titanium, screw-shaped inplants were used in this study. Twenty-four New Zealand white mature male rabbits were used. The inplants were inserted into the articular femoral knee joint according to a previously described technique. Each rabbit received 2 inplants, 1 test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
112
1
8

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(130 citation statements)
references
References 11 publications
9
112
1
8
Order By: Relevance
“…These studies confirm that roughening of the titanium dental implants increases their mechanical fixation to the bone, but not their biological fixation. [18][19][20] A. Karacs et al 21 investigated the morphology of machined, blasted and laser-treated surfaces of titanium. The Al 2 O 3 blasted surface has a unique surface morphological characteristic that enhances the osseointegration process.…”
Section: Abrasive Blastingmentioning
confidence: 99%
“…These studies confirm that roughening of the titanium dental implants increases their mechanical fixation to the bone, but not their biological fixation. [18][19][20] A. Karacs et al 21 investigated the morphology of machined, blasted and laser-treated surfaces of titanium. The Al 2 O 3 blasted surface has a unique surface morphological characteristic that enhances the osseointegration process.…”
Section: Abrasive Blastingmentioning
confidence: 99%
“…[4][5][6][7][8][9] Further increasing surface roughness does not result in an increase in bone-implant contact, and may result in decreased implant retention. 10,11 We propose that osteoblasts encountering a very rough surface may actually interact with an area of smoother surface between the peaks and, therefore, perceive the surface as smooth.…”
mentioning
confidence: 99%
“…Grit-blasted implants have been reported to exhibit improved reactivity on the titanium surface due to removal of contaminants on the surface layer and production of fine irregular unevenness on the surface by blasting with titanium oxide or alumina oxide 40) . Another study suggested that the bone/implant contact area is larger in grit-blasted implants than machined implants, and therefore, cells on the rough surface can exist and proliferate for a longer period 41) .…”
Section: Discussionmentioning
confidence: 99%